RASIO LEGIS HUKUM WARIS ADAT BALI SEORANG AHLI WARIS YANG PINDAH AGAMA - Mayasari, Dian Ety; Lyanthi, Merline Eva (Jurnal Hukum Bisnis Bonum Commune, 2021)
AbstractThis study aims to know and understand that the heirs who convert to religions in Balinese customary law have their rights and obligations in the family environment. In Balinese customary law, the rights and obligations of the heir must accept both material and immaterial forms and this if the heir who is a Hindu changes to another religion, a legal problem will arise. The research method used is juridical normative based on legal principles, legal principles and rules of Balinese traditional inheritance law that exist in awig-awig customary villages. The results showed that according to Balinese traditional inheritance law, heirs who converted to religions were no longer the heirs. The loss of position as an heir as a result of changing religions occurs because when someone changes religion, automatically the inheritance rights of the parents will be lost as a result of not being allowed to carry out religious-related obligations to the family related to ancestral worship in Sanggah/Eksajan/Temples and to local indigenous communities related to religious and customary activities. The loss of inheritance rights from parents as a result of changing religions is also caused because Balinese traditional inheritance law adheres to a patrilineal kinship system, not just purusa (male) and prime (female) status, but is much more complex, concerning scale (reality) and niskala (belief). So that according to Balinese customary inheritance law, rules apply to heirs who change religions where the position of the heir dies in the kingdom or someone who changes religion from Hinduism to another religion will result in losing the right to inheritance.Keywords : inheritance law; heirs; balinese customsAbstrakPenelitian ini memiliki tujuan untuk mengetahui dan memahami sebagai ahli waris yang pindah agama dalam Hukum Adat Bali mempunyai hak dan kewajibannya di lingkungan keluarga. Dalam Hukum Adat Bali hak dan kewajiban dalam ahli waris harus menerima secara bersamaan baik berbentuk materiil maupun immateriil dan ini jika ahli waris yang beragama Hindu pindah agama lain maka akan muncul suatu permasalahan hukum yang diteliti. Metode penelitian yang dipakai ialah yuridis normatif berdasarkan asas-asas hukum, kaidah-kaidah hukum dan peraturan-peraturan hukum waris adat Bali yang ada dalam awig-awig desa adat. Hasil penelitian menunjukkan bahwa menurut hukum waris adat Bali terhadap ahli waris yang pindah agama tidak lagi sebagai ahli waris. Hilangnya kedudukan sebagai ahli waris akibat dari pindah agama ini terjadi karena ketika seseorang pindah agama maka secara otomatis hak waris dari orang tua akan hilang sebagai akibat dari tidak boleh melaksanakan kewajiban-kewajiban yang berhubungan dengan keagamaan kepada keluarga terkait persembahyangan memuja leluhur di Sanggah/Pemerajan/Pura dan kepada masyarakat adat setempat terkait kegiatan keagamaan dan adat. Hilangnya hak waris dari orang tua sebagai akibat dari pindah agama juga diakibatkan karena hukum waris adat Bali menganut sistem kekeluargaan patrilineal, tidak juga sekedar status purusa (laki-laki) dan perdana (perempuan), melainkan jauh lebih kompleks, menyangkut sekala (kenyataan) dan niskala (kenyakinan). Sehingga menurut hukum waris adat Bali berlaku aturan-aturan terhadap ahli waris yang berpindah agama dimana kedudukan ahli waris ninggal kedaton atau seseorang yang pindah agama dari agama Hindu ke agama yang lain akan  mengakibatkan kehilangan hak mewaris.Kata kunci: adat Bali; ahli waris; hukum waris